From Scratch to Python : Lego Robots as Motivational Tools for Coding - Körei, Attila; Szilágyi, Szilvia (Multidiszciplinaris Tudomanyok, 2022)
Educational Robotics is a specific interdisciplinary field that improves learning experience and develops student skills and competences through robotic-based activities. Constructing of robot models provide hands-on experiences for children while programming the built model teach basic coding knowledge for them. Instead of use text-based programming languages coding can be learned by a Scratch-based language in an age-appropriate way. Educational robots are excellent tools of introducing and teaching programming at all levels of education, though most of them aim at pupils in primary and secondary schools. LEGO Education's products also stand out among the educational robots thanks to their high quality and the very wide range of projects and teaching materials. The recently released Lego robot, SPIKE Prime, can also be programmed in Python, providing a playful way to learn the basics of object-oriented programming even in higher education.